MANAJEMEN PEMBELAJARAN AKTIF BERBASIS KARAKTER - Febriantina, Susan (Universitas Djuanda Bogor, 2018)
This research is to get factual data about the planning, implementation, supervision, and some problems of character-based active learning management at independent curriculum 2013 junior high schools in Depok. This research uses descriptive method. The result showed that character-based active learning management consists of learning planning, implementation, and supervisions which derived from unique school values.